The impact of vaccine booster doses on specific B- and T-lymphocyte dynamics in Thai healthcare personnel following COVID-19 vaccination - Wanitchaya Kittikraisak; Chaniya Leepiyasakulchai; Chutiphon Saelee; Chuleekorn Tanathitikorn; Patama Suttha; Somsak Punjasamanvong; Phunlerd Piyaraj; Thanapat Wongrapee; Pornsak Yoocharoen; Suthat Chottanapund; Joshua A. Mott (Scientific Reports)
Abstract A primary series of Sinovac COVID-19 vaccine (CoronaVac) and ChAdOx1 nCoV-19 (Oxford-AstraZeneca) vaccine successfully increased anti-spike antibodies, neutralizing antibodies, and T-lymphocytes, as was also observed following booster doses of Oxford-AstraZeneca or BNT162b2 (Pfizer-BioNTech) vaccine. However, information regarding the dynamics of specific B- and T-lymphocytes induced by additional vaccinations remains limited. We examined the dynamics of specific B- and T-lymphocyte subsets induced by primary series vaccinations and booster doses over a two-year period of COVID-19 vaccination among healthcare personnel (HCP) enrolled in a prospective cohort study in Thailand. HCP, recruited between January and March 2021, had blood specimens collected at enrollment and at three-month intervals for cellular immune response testing. COVID-19 vaccinated participants (verified against documentation) were grouped by vaccination schedules: (A) CoronaVac with Oxford-AstraZeneca vaccine as the first booster dose (n = 46), (B) CoronaVac with Pfizer-BioNTech vaccine as the first booster dose (n = 53), and (C) Oxford-AstraZeneca vaccine (n = 29). All three groups had up to four subsequent booster doses of either the same or different platforms. Following the B-lymphocyte enzyme-linked immunospot and the T-lymphocyte intracellular cytokine staining assays, SARS-CoV-2 spike 1 (S1)- and receptor-binding domain (RBD)-specific antibody-secreting B-lymphocytes, and Interferon Gamma (IFN-Ƴ)- and/or Tumor Necrosis Factor Alpha (TNF-α)-producing T-lymphocytes for all blood collection time points were counted. Among participants without evidence of infection (i.e.,  those who tested negative for SARS-CoV-2 antibodies prior to vaccination and those who tested negative by SARS-CoV-2 real-time reverse transcription polymerase chain reaction during the study), levels of cellular immune response during weeks 1–12 since the last vaccine dose were compared between vaccine doses using the Kruskal–Wallis test. In all three groups, compared to the primary series, the first booster dose induced significant SARS-CoV-2 antigen-specific antibody-secreting B-lymphocyte counts (range 4.2–9.0-fold increase) but non-significant S1-specific cytokine-producing T-lymphocyte counts (range 0.5–1.3-fold). There were no notable differences in both antigen-specific antibody-secreting B-lymphocyte and specific cytokine-producing T-lymphocyte counts following the second, third, and fourth booster doses in all three groups compared to the first booster dose. Initial COVID-19 booster doses were essential for overall increases in the peak counts of antigen-specific B-lymphocytes, prior to minimal contraction phases occurred following additional boosters, while antigen-specific T-lymphocyte counts maintained a consistently high levels of immune response. The second, third, and fourth booster doses restored the levels of both B- and T-lymphocytes after the immune responses waned in a time-dependent manner.